т.синусов:
a / sin(альфа) = b / sin(бета) = c / sin(гамма)
a*sin(бета) = b*sin(альфа)
b = a*sin(бета) / sin(альфа)
S = (1/2) * ab*sin(гамма) = a*a*sin(бета)*sin(гамма) / (2sin(альфа))
a = корень(2*S*sin(альфа) / (sin(бета)*sin(гамма)))
аналогично...
b = корень(2*S*sin(бета) / (sin(альфа)*sin(гамма)))
c = корень(2*S*sin(гамма) / (sin(альфа)*sin(бета)))
S = a*h(a) / 2 (здесь h(a) ---высота, проведенная к стороне а...)
h(a) = 2S / a
h(a) = корень( 2*S*sin(бета)*sin(гамма) / sin(альфа) )
аналогично высота, проведенная к стороне b
h(b) = корень( 2*S*sin(альфа)*sin(гамма) / sin(бета) )
высота, проведенная к стороне c
h(c) = корень( 2*S*sin(альфа)*sin(бета) / sin(гамма) )
т.синусов:
a / sin(альфа) = b / sin(бета) = c / sin(гамма)
a*sin(бета) = b*sin(альфа)
b = a*sin(бета) / sin(альфа)
S = (1/2) * ab*sin(гамма) = a*a*sin(бета)*sin(гамма) / (2sin(альфа))
a = корень(2*S*sin(альфа) / (sin(бета)*sin(гамма)))
аналогично...
b = корень(2*S*sin(бета) / (sin(альфа)*sin(гамма)))
c = корень(2*S*sin(гамма) / (sin(альфа)*sin(бета)))
S = a*h(a) / 2 (здесь h(a) ---высота, проведенная к стороне а...)
h(a) = 2S / a
h(a) = корень( 2*S*sin(бета)*sin(гамма) / sin(альфа) )
аналогично высота, проведенная к стороне b
h(b) = корень( 2*S*sin(альфа)*sin(гамма) / sin(бета) )
высота, проведенная к стороне c
h(c) = корень( 2*S*sin(альфа)*sin(бета) / sin(гамма) )